Comparative study using autologous platelet-rich fibrin and titanium prepared platelet-rich fibrin in the treatment of infrabony defects: An in vitro and in vivo study - Dipika Kalyan Mitra; Priyanka Nandkumar Potdar; Saurabh Suresh Prithyani; Silvia Victor Rodrigues; Gaurav Prabhakar Shetty; Meenakshi Abhay Talati (Wolters Kluwer Medknow Publications, 2019)
Background: The platelet concentrates had been pioneered to be used in regenerative medicine since above a decade. Aims and Objectives: To compare the autologous platelet rich fibrin (PRF) and titanium prepared platelet rich fibrin (T-PRF) in the treatment of infrabony defects, clinically and radiographically and to compare the histologic difference between PRF and T-PRF by light microscopy and scanning electron microscopy (SEM). Materials and Methods: The present study is a split mouth randomised controlled trial study in which 20 sites were selected and randomly assigned equally into 10 sites each in group A [Test group=T-PRF] and group B [Control group=PRF]. Clinical parameters were evaluated at baseline,3 months and 9 months. Radiographic parameters were evaluated at baseline and 9 months. Histologic differences between light microscopy and SEM for both PRF and T-PRF was studied after sequential processing. Results: There was marked reduction in Probing Pocket depth and gain in Clinical Attachment Level in both the T-PRF and PRF groups from baseline to 9 months in intragroup comparisons. However, on intergroup comparisons, no statistical significance was seen. Radiographically, mean defect depths for both the groups showed statistically significant reduction from baseline values to 9 months on intragroup comparisons but not on intergroup comparisons. In-vitro evaluation, on both light and scanning electron microscopy, T-PRF showed denser fibril meshwork as compared to PRF. Conclusion: The clinical parameters and radiographic outcomes showed marked improvement at 9 months with both PRF and T-PRF in the treatment of infrabony defects from baseline values in intragroup comparison. However, statistically efficacy of T-PRF was not seen to be superior to that of PRF both clinically and radiographically. Histologic evaluation showed T-PRF had denser fibrils as compared to PRF in both light and scanning electron microscopy.